Software reliability growth modeling for agile software development - Rawat, Shubham; Goyal, Nupur; Ram, Mangey (Zielona Góra: Uniwersytet Zielonogórski)
The frequent incremental release of software in agile development impacts the overall reliability of the product. In this paper, we propose a generic software reliability model for the agile process, taking permanent and transient faults into consideration. The proposed model is implemented using the NHPP (non-homogenous Poisson process) and the Musa model. The comparison of the two implementations yields an effective, empirical and reliable model for agile software development.
Keywords: software reliability; testing; non-homogeneous poison process; transient faults; permanent faults; Musa model